Weighing evidence and assessing uncertainties. (June 2016) - Dorne, Jean Lou C. M.; Bottex, Bernard; Merten, Caroline; Germini, Andrea; Georgiadis, Nikolaos; Aiassa, Elisa; Martino, Laura; Rhomberg, Lorenz; Clewell, Harvey J.; Greiner, Matthias; Suter, Glenn W.; Whelan, Maurice; et al.
Abstract: Methodologies for integrating (weighing) evidence and assessing uncertainties are of utmost importance to ensure that scientific assessments are transparent, robust and fit for purpose to support decision‐makers. One of the key challenges remains the development of harmonised methodologies for both weighing scientific evidence and assessing uncertainties in the food safety area mainly because of the multidisciplinary and complex nature of the topics involved. The breakout session 'Weighing evidence and assessing uncertainties' was held at the EFSA 2nd Scientific Conference 'Shaping the Future of Food Safety, Together'. This paper aims at summarising the contributions of this breakout session and formulates recommendations to further support the development of harmonised methodologies and practical applications for weighing evidence and analysing uncertainty in key areas of food safety, including chemical risk assessment, microbiological risk assessment and environmental risk assessment.